Dentigerous cyst in the maxilla: case report in a pediatric patient (Research, Society and Development, 2021)
Dentigerous cysts are the second most common odontogenic cysts of the jaws, and sometimes inhibit the eruption of teeth. Almost all of the dentigerous cyst encloses the crown of an unerupted tooth and the radiolucent area is attached to the tooth at the cementoenamel junction. Dentigerous cyst is more common in male patients and most commonly develop in the second and third decades of life. Clinically, a localized swelling of the alveolar bone can be detected, however, dentigerous cysts can be asymptomatic during a long period of time, leading to a significant destruction of bone. The conventional treatment plan is cyst removal and marsupialization. Marsupialization therapy can be useful to promote the spontaneous eruption of the involved tooth within the cyst. However, tooth eruption does not always occur spontaneously after marsupialization. This article aims to report a clinical case of the diagnosis and treatment of a dentigerous cyst in the maxilla associated with an unerupted canine in a pediatric patient and discussion of the treatment performed.